Mesenchymal stromal cells for sepsis and septic shock: Lessons for treatment of COVID-19. (18th August 2020) - Laroye, Caroline; Gibot, Sébastien; Huselstein, Céline; Bensoussan, Danièle
Abstract: Sepsis is defined as life-threatening organ dysfunction caused by a deregulated immune host response to infection. The emergence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has highlighted this multifactorial and complex syndrome. The absence of specific treatment neither against SARS-CoV-2 nor against acute respiratory distress syndrome (ARDS), the most serious stage of this infection, has emphasized the need to find alternative treatments. Several therapeutics are currently being tested, including mesenchymal stromal cells. These cells, already used in preclinical models of ARDS, sepsis, and septic shock and also in a few clinical trials, appear well-tolerated and promising, but many questions remain unanswered. :